Toward strategical bottom-up synthesis of carbon materials with exceptionally high basal-nitrogen content: Development of screening techniques. (25th January 2023) - Yamada, Yasuhiro; Sato, Hayato; Gohda, Syun; Taguchi, Taisei; Sato, Satoshi
Abstract: Selective doping of nitrogen-containing functional groups in the basal plane of carbon materials is the most promising technique for enhancing performances and stability significantly for various applications such as catalysts and electrodes. Reported carbon materials with controlled basal nitrogen are generally synthesized on substrates, leading to low productivity and high cost. Therefore, simple preparation methods for selective doping of nitrogen in the basal plane of carbon materials without substrates are in great demand. This work achieved that simple heat treatment of indolizino[6, 5, 4, 3- ija ]quinoline (IQ) at 973 K formed a carbon material with an exceptionally high basal-nitrogen content (98-92%). The highly selective doping of basal nitrogen was attained because of the presence of stable tertiary nitrogen in one pentagon and two hexagon rings of IQ. Screening precursors for preparing carbon materials with a high basal-nitrogen content was conducted to minimize research costs. Screening of precursors by molecular dynamic simulation with reactive force field and formation energies of scission of C–N bonds revealed that IQ was the best precursor to maintain the high percentage of tertiary nitrogen in the basal plane after carbonization because of the high stability of C–N bonds in IQ. Thus, strategic synthesis is now possible using the screening techniques. Graphical abstract: Image 1